Cancer Cell Mitochondria Targeting by Pancratistatin Analogs is Dependent on Functional Complex II and III - Ma, Dennis (Sci Rep, 2017)
Enhanced mitochondrial stability and decreased dependence on oxidative phosphorylation confer an acquired resistance to apoptosis in cancer cells, but may present opportunities for therapeutic intervention. The compound pancratistatin (PST) has been shown to selectively induce apoptosis in cancer cells. However, its low availability in nature has hindered its clinical advancement. We synthesized PST analogs and a medium-throughput screen was completed. Analogs SVTH-7, -6, and -5 demonstrated potent anti-cancer activity greater than PST and several standard chemotherapeutics. They disrupted mitochondrial function, activated the intrinsic apoptotic pathway, and reduced growth of tumor xenografts in vivo. Interestingly, the pro-apoptotic effects of SVTH-7 on cancer cells and mitochondria were abrogated with the inhibition of mitochondrial complex II and III, suggesting mitochondrial or metabolic vulnerabilities may be exploited by this analog. This work provides a scaffold for characterizing distinct mitochondrial and metabolic features of cancer cells and reveals several lead compounds with high therapeutic potential.